2006
DOI: 10.1897/04-530r.1
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of aqueous methylmercury influences uptake by a freshwater alga (Selenastrum capricornutum)

Abstract: Uptake of methylmercury (MeHg) by the alga Selenastrum capricornutum was measured in freshwater batch culture bioassays. The concentration of MeHg in the alga increased rapidly (within 15 min), reached a maximum by 6 h, and then declined because of growth dilution. The alga's rapid growth rate (doubling time, approximately 10 h) contributed to the importance of growth dilution. Conditional first-order rate constants were calculated for uptake (k1 = 6.95 x 10(-9) L/cell/h) and growth (kG = 0.07/h). A competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 38 publications
5
42
0
2
Order By: Relevance
“…Both chloride (85 g L 21 ) and DOC (42 mg L 21 ) are very high in the mixed layer, and both of these influence Hg speciation and uptake, but not always in predictable ways (Aiken et al 2003;Pickhardt and Fisher 2007;Luengen et al 2012). Although DOC can help maintain Hg in solution, its reactivity and concentration influence biotic uptake of MeHg (Gorski et al 2006). Consequently, more work will need to be done to understand whether the MeHg accumulated by Artemia is from particles delivered from the deep brine layer, or by reactions in the mixed layer that transform the dissolved advected Hg into particles or molecules that can be taken up by these organisms.…”
Section: Depth or Treatmentmentioning
confidence: 99%
“…Both chloride (85 g L 21 ) and DOC (42 mg L 21 ) are very high in the mixed layer, and both of these influence Hg speciation and uptake, but not always in predictable ways (Aiken et al 2003;Pickhardt and Fisher 2007;Luengen et al 2012). Although DOC can help maintain Hg in solution, its reactivity and concentration influence biotic uptake of MeHg (Gorski et al 2006). Consequently, more work will need to be done to understand whether the MeHg accumulated by Artemia is from particles delivered from the deep brine layer, or by reactions in the mixed layer that transform the dissolved advected Hg into particles or molecules that can be taken up by these organisms.…”
Section: Depth or Treatmentmentioning
confidence: 99%
“…Intensive fishing has been suggested as a way of decreasing Hg bioaccumulation in aquatic food webs (Schindler et al, 1995), since removal of fish has been shown to diminish competition and increase food availability, which in turn has led to higher fish growth rates and greater dilution of Hg (Verta, 1990;Therien et al, 2003;Mailman et al, 2006;Lepak et al, 2009). Similarly, rapid growth of algal colonies and greater densities of algal cells have been associated with dilution of their Hg concentrations (Pickhardt et al, 2002;Hill and Larsen, 2005;Gorski et al, 2006). Conversely, in areas of low primary productivity and poor nutrient quality, slow rates of growth are correlated with higher concentrations of Hg in algae, which are transferred to higher trophic level organisms such as zooplankton (Pickhardt et al, 2005;Karimi et al, 2007).…”
Section: Growth Rates and Lifespan Of Organismsmentioning
confidence: 99%
“…The resultant formation of natural complexes influences uptake of many metals by biota. Prior research suggests that phytoplankton MeHg uptake occurs primarily via passive diffusion of neutral complexes across a cell membrane (Fisher and Reinfelder, 1995;Gorski et al, 2006;Lawson and Mason, 1998;Mason et al, 1996;Pickhardt and Fisher, 2007). Passive uptake of both species could also result after sorption of Hg and MeHg to cell surfaces (Fisher, 1985).…”
Section: Introductionmentioning
confidence: 99%